Cobalt nanoclusters deposit on nitrogen-doped graphene sheets as bifunctional electrocatalysts for high performance lithium – oxygen batteries - Palani, Raja; Wu, Yi–Shiuan; Wu, She–Huang; Chang, Jeng-Kuei; Jose, Rajan; Yang, Chun-Chen (Elsevier Ltd, 2025)
Rechargeable lithium-oxygen (Li-O2) batteries are being considered as the next-generation energy storage systems due to their higher theoretical energy density. However, the practical application of Li-O2 batteries is hindered by slow kinetics and the formation of side products during the oxygen reduction and evolution reactions on the cathode. These reactions lead to high overpotentials during charging and discharging. To address these challenges, we propose a simple ultrasonic method for synthesizing cobalt nanoclusters embedded in nitrogen-doped graphene nanosheets (GrZnCo) derived from metal-organic frameworks (MOFs). The resulting material, due to the retention of metallic cobalt structure, exhibits better electronic conductivity. Additionally, the GrZnCo catalyst shows vigorous catalytic activity, which can improve reaction kinetics and suppress side reactions, thus lowering the charging overpotential. We have investigated the impact of different catalyst compositions (GrZnCox; x = 1, 3, 5) by varying the amounts of cobalt and zinc. The optimum catalyst, GrZnCo3,